2020
DOI: 10.1371/journal.pone.0233060
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors for underweight among children under-five in a resource limited setting: A community based case control study

Abstract: Previous studies conducted in Nepal have not identified the potential maternal risk for underweight among children under-five years of age in resource-poor settings. Therefore, to identify these risk factors for being underweight among children under-five years old, a community-based case-control study was conducted in a rural village in the Chitwan District in Nepal. Cases were defined as children who were diagnosed as underweight based on low weight per age, whereas controls were the children with normal wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
3
1
0
Order By: Relevance
“…Also, the prevalence of underweight and wasting in males was higher than that of girls, which is in line with the study conducted by Ahmadi et al (5). Moreover, among children with a history of acute respiratory infection and diarrhea during the past 2 weeks, the prevalence of underweight and wasting was significantly higher than among children without a history of these diseases, this result is not far from expectation and is in line with the results of other studies [5,25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, the prevalence of underweight and wasting in males was higher than that of girls, which is in line with the study conducted by Ahmadi et al (5). Moreover, among children with a history of acute respiratory infection and diarrhea during the past 2 weeks, the prevalence of underweight and wasting was significantly higher than among children without a history of these diseases, this result is not far from expectation and is in line with the results of other studies [5,25].…”
Section: Discussionsupporting
confidence: 91%
“…This research’s findings indicated that the prevalence of stunting among children whose family income was lower than the adequate level of life is higher than children whose family income was sufficient, this result was not far from expectation and is in line with the results of many studies in this field [ 22 , 25 ]. Even in some research, it was noted that family income is a stronger factor in identifying children’s nutritional status than mothers’ nutritional knowledge [ 22 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A previous study observed that the prevalence of underweight and overweight women aged 15-49 years in Bangladesh was 22•4 % and 14•1 %, respectively. These conditions are crucial for determining the overall health condition of a child, as maternal health status plays a significant role in child health (39) . Our study also demonstrated that maternal education was a significant factor for controlling the DBM.…”
Section: Discussionmentioning
confidence: 99%